Targeted application of GO to improve mechanical and thermal properties of PVCS/RS composites. (3rd April 2023) - Sheydaei, Milad; Pouraman, Vahid; Edraki, Milad; Alinia-Ahandani, Ebrahim; Asadi-Sadeh, Seyedeh Mozhdeh
Abstract: In this study, wood–plastic composites (WPCs) were prepared from polyvinyl chloride (PVC) modified by sodium trisulfide (Na2 S3 ) and rice straw (RS) treated with 7% sodium hydroxide solution. The results showed that after modification, 35.4 wt. % of sulfur is present in the structure of PVC containing sulfur (PVCS). The structural, morphological, thermal, and mechanical properties of the samples were investigated. As the RS fibers content in the composites increased, the thermal stability also increased but the mechanical properties decreased slightly. Moreover, the presence of sulfur in the matrix created antifungal properties that the results showed us that the PVCS can inhibit and kill Aspergillus niger and Aspergillus brasiliensis . Also, graphene oxide (GO) was added to the matrix to improve its properties. The addition of GO to composite improved the mechanical and thermal properties to extent that its mechanical properties were better than the sample without RS. Graphical Abstract: UF0001